Efficient hydrogen production using photosystem I enhanced by artificial light harvesting dye. Issue 2 (11th January 2019) - Nagakawa, Haruki; Takeuchi, Ayano; Takekuma, Yuya; Noji, Tomoyasu; Kawakami, Keisuke; Kamiya, Nobuo; Nango, Mamoru; Furukawa, Rei; Nagata, Morio
Abstract : In this study, we improved the hydrogen production efficiency by combining a photosystem I/platinum nanoparticle composite with an artificial light harvesting dye, Lumogen Red. Abstract : In this study, we improved the hydrogen production efficiency by combining photosystem I with an artificial light harvesting dye, Lumogen Red. In the reaction system, Lumogen Red allows light absorption and energy transfer to photosystem I by Förster resonance energy transfer; therefore, the Pt nanoparticles act as active sites for hydrogen generation.